2013
DOI: 10.1175/jas-d-12-0226.1
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Resolving Mesoscale Latent Heating in the North Atlantic Storm Track

Abstract: Theoretical, observational, and modeling studies have established an important role for latent heating in midlatitude cyclone development. Models simulate some contribution from condensational heating to cyclogenesis, even with relatively coarse grid spacing (on the order of 100 km). Our goal is to more accurately assess the diabatic contribution to storm-track dynamics and cyclogenesis while bridging the gap between climate modeling and synoptic dynamics. This study uses Weather Research and Forecasting model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
129
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 62 publications
(56 reference statements)
11
129
1
Order By: Relevance
“…This result is in general agreement with the work by Jung et al (2006) and Willison et al (2013) as discussed in Sect. 1.…”
Section: Sensitivity To Horizontal Resolutionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is in general agreement with the work by Jung et al (2006) and Willison et al (2013) as discussed in Sect. 1.…”
Section: Sensitivity To Horizontal Resolutionsupporting
confidence: 93%
“…This behaviour suggests that important physical processes in the development of the storm are not well reproduced by the coarse resolution model. The work by Willison et al (2013) suggests that the lack of diabatic contributions along insufficiently resolved frontal rain bands is a likely cause. This may be particularly important for Jeanette, as it occurred in October when baroclinicity is usually still relatively low, but sea surface temperatures are high.…”
Section: Results For Echam6 At T63 Horizontal Resolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, poor representation of latent heating can have a significant influence on the evolution of ETCs in models. Willison et al (2013), investigating the impact of resolving mesoscale heating features within ETCs in the Atlantic stormtrack, found that a higher resolution model which was able to better represent these features produced a more vigorous stormtrack. The representation of latent heating within ETCs may therefore impact on the representation of the wider environment in the extratropics in climate models.…”
Section: • Composite Etcs From Cloudsat Indicate That Neithermentioning
confidence: 99%